Maternal Mortality: A 5-year analysis at a District Headquarter Hospital in Pakistan - Ikram, Saiqa; Wahid, Nazia; Ali, Sobia; Ali, Sofia (Journal of Ayub Medical College Abbottabad, 2021)
Background: Maternal mortality ratio is an important figure reflecting the strength of a healthcare system. Traditionally the causes of maternal death are described by the three-delay model. This study was conducted to evaluate the causes and determinants of maternal mortality at a secondary level hospital in a rural area of northern Pakistan over a period of 5 years (2013-17). Methods: This cross-sectional study was conducted in 2018 on hospital data for the previous 5 years (2013-17) regarding mortality in the Gynaecology department of District Headquarter hospital, Timergara. Cases of maternal death were identified and secondary data was retrieved from the hospital records and patient case sheets. Results: Forty-seven cases of maternal death were identified over a period of 5 years and the average maternal mortality ratio calculated to be 110/100,000 live births. Haemorrhage was the commonest cause (36%) followed by uterine rupture (34%) and hypertensive disorders (21%). Most of the cases seen were in uneducated women belonging to the poor socioeconomic stratum (85%) aged 20 to 35 years (55%). 51% of the women were multigravidae coming from within a distance of 25-50 km from the hospital (53%) Majority of the dying mothers (57%) had no antenatal care and were seen arriving at the hospital in the evening shifts (48%). Conclusions: Causes and determinants of maternal death are complex and inter sectorial. Poverty, lack of education, antenatal care, family spacing and prompt access to emergency care contribute to maternal death. Keywords: Maternal death; Maternal mortality; Causes; Determinants; Rural area; Pakistan